Mitigation of Ionospheric Threats to GNSS an Appraisal of the Scientific and Technological Outputs of the TRANSMIT Project - Notarpietro, Riccardo; Dovis, Fabio; De Franceschi, Giorgiana; Aquino, Marcio (IntechOpen, 2014)
TRANSMIT (Training Research and Applications Network to Support the Mitigation of Ionospheric Threats) is an initiative funded by the European Commission through a Marie Curie Initial Training Network. It provided a coordinated program of academic and industrial training, focused on atmospheric phenomena that can significantly impair a wide range of systems and applications that are at the core of several activities embedded in our daily life. TRANSMIT deals with the harmful effects of the ionosphere on these systems. Main aim of the project has been to develop a web based prototype demonstrator aiming to showcase the project research outcomes in a user friendly manner, through a series of model outputs and tools that could serve as the blueprint for a future service to assist users and industry to mitigate the effects of ionospheric threats to GNSS.